2017
DOI: 10.1016/j.etap.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in the mesohippocampal dopamine circuit following exposure to the brominated flame retardant, HBCDD

Abstract: Many chemicals have been used to increase the safety of consumer products by reducing their flammability and risk for ignition. Recent focus on brominated flame retardants, such as polybrominated diphenyl ethers (PBDEs) has shown them to contribute to neurobehavioral deficits in children, including learning and memory. As the manufacture and use of PBDEs has been reduced, replacement chemicals, such as hexabromocyclododecane (HBCDD) have been substituted. Our current study evaluated the neurotoxicity of HBCDD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(105 reference statements)
0
9
0
Order By: Relevance
“…Firstly, neurotransmission as an important mechanism how neuron conducts message and the impact on this can be known by measuring neurotransmitters as a biomarker (Boix et al 2010;Dingemans et al 2007;Gee et al 2011;Lei et al 2017;Moser et al 2015;Pham-Lake et al 2017;Wang et al 2015;Zhang et al 2018;Zhu et al 2018). Secondly, neurochannels balance ionic concentration inside and outside of the cell through voltage gated calcium channels and calcium could be a biomarker to study the ion channel mechanism (Mochida 2000;Dingemans et al 2007).…”
Section: Translational In Vivomentioning
confidence: 99%
“…Firstly, neurotransmission as an important mechanism how neuron conducts message and the impact on this can be known by measuring neurotransmitters as a biomarker (Boix et al 2010;Dingemans et al 2007;Gee et al 2011;Lei et al 2017;Moser et al 2015;Pham-Lake et al 2017;Wang et al 2015;Zhang et al 2018;Zhu et al 2018). Secondly, neurochannels balance ionic concentration inside and outside of the cell through voltage gated calcium channels and calcium could be a biomarker to study the ion channel mechanism (Mochida 2000;Dingemans et al 2007).…”
Section: Translational In Vivomentioning
confidence: 99%
“…GD0‐PND21 (Maurice et al., 2015), GD1‐PND0 (Miller‐Rhodes et al., 2014) and PND10‐PND70 (Zhang et al., 2017a), followed by behavioural analyses of the offspring at different ages. One study exposed adult animals for 6 weeks (Pham‐Lake et al., 2017) (see Table 10 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Pham‐Lake et al. (2017) reported that 2‐month old male mice dosed with 25 mg/kg bw per day HBCDDs by gavage for 6 weeks, followed by a further 6 weeks without dosing, did not exhibit explicit behavioural abnormalities such as deficits in grooming, isolation, feeding or generalised movement. The absence of these effects does not necessarily contradict those observed by Eriksson et al.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings highlight VMAT2 as a vulnerable target to environmental toxicants (Caudle 2015;Caudle et al 2012). Animal studies suggest that a range of chemical exposures including pesticides, fungicides, polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDE's), and perfluorinated compounds reduce the expression and function of VMAT2 and lead to symptoms closely resembling Parkinson's Disease (PD) (Bradner et al 2013;Caudle et al 2005;Choi et al 2015;Enayah et al 2018;Inamdar et al 2013;Miller et al 1999;Patel et al 2016;Pham-Lake et al 2017;Richardson et al 2006;Richardson et al 2008;Richardson and Miller 2004;Schuh et al 2009;Wilson et al 2014;Xiong et al 2016). Continued research into the effects of these chemicals on the function of amine transporters should improve our understanding of how they function to disrupt the vesicular integrity of the synaptic vesicle.…”
Section: Introductionmentioning
confidence: 99%